Electrophysiological Biomarkers of Epileptogenicity in Alzheimer’s Disease - Yu, Tingting; Liu, Xiao; Wu, Jianping; Wang, Qun (Frontiers in Human Neuroscience, 2021)
Cortical network hyperexcitability is an inextricable feature of Alzheimer’s disease (AD) that also might accelerate its progression. Seizures are reported in 10-22% of AD patients, and subclinical epileptiform abnormalities have been identified in 21-42% of AD patients without seizures. Accurate identification of hyperexcitability and appropriate intervention to slow the compromise of cognitive functions of AD might open up a new approach to treatment. Based on the results of several studies, epileptiform discharges, especially those with specific features (including high frequency, robust morphology, right temporal location, and occurrence during awake or rapid eye movement states), frequent small sharp spikes (SSSs), temporal intermittent rhythmic delta activities (TIRDAs), and paroxysmal slow wave events (PSWEs) recorded in long-tern scalp electroencephalogram (EEG) provide sufficient sensitivity and specificity in detecting cortical network hyperexcitability and epileptogenicity of AD. In addition, magnetoencephalogram (MEG), foramen ovale (FO) electrodes, and computational approaches help to find subclinical seizures that are invisible on scalp EEGs. We perform a comprehensive analysis of the aforementioned electrophysiological biomarkers of AD related seizures.